Knowledge and Process Management in Health Care Organizations - Stefanelli, M. (Methods of Information in Medicine, 2004)
Objective: Medical knowledge management and care process management have become to be considered as valuable strategic assets that can lead to sustained increase in Health Care Organization (HCO) performance. Thus, it is essential to investigate which are the enablers for promoting knowledge-based organizations (people, organization, process, and system perspectives). Although they are essential for a HCO to manage knowledge effectively, it is still unclear how to employ them in more principled fashion. This requires innovative management strategies to determine effective ways of utilizing knowledge resources and capabilities available both within and outside the organization.Method: This paper reviews knowledge and process management theories, methods, and technologies that are potentially effective in building high performance HCOs. They come from a variety of fields behind computer science and medical informatics, e.g. from business and organization sciences to psychological and cognitive sciences, from epistemology to sociology. However, the success in developing future Health Information Systems (HIS) requires their incorporation into a new conceptual framework after recognizing how peculiar are the characteristics of HCOs with respect to other organizations. Investigating the nature of knowledge, in general, and of medical knowledge, in particular, is essential to define which services the future HIS should provide to foster collaboration between patients and health professionals. The knowledge creation process is then described in order to emphasize its dynamic and social characteristics. The potential of workflow technology for building innovative HISs is analyzed together with several basic research issues which are very challenging for researchers in the field.Result: A framework for augmenting the conceptual analysis of theories, methods, tools and effects of knowledge management in building high performance HCOs.
Keywords: Knowledge management; process management; communication models and infrastructures; hospital information systems; collaborative work; careflow management systems